Quantitative cellular-resolution map of the oxytocin receptor in postnatally developing mouse brains - Kyra T. Newmaster; Zachary T. Nolan; Uree Chon; Daniel J. Vanselow; Abigael R. Weit; Manal Tabbaa; Shizu Hidema; Katsuhiko Nishimori; Elizabeth A. D. Hammock; Yongsoo Kim (Nature Communications, 2020)
The oxytocin receptor plays an important role in establishing mature neural circuits for social behavior during the early postnatal period. Here, the authors develop digital reference brains for different postnatal ages and provide a quantitative brain-wide map of oxytocin receptor expression in early postnatal and adult mouse brains.